Generative artificial intelligence for education: The present and the future - Reynaud, Teresa Vaz (2024)
The advancements in generative artificial intelligence (genAI) technologies, such as ChatGPT, DALL-E, Bing AI, and Copilot, have significantly disrupted various sectors, including education. These tools are capable of generating human-like content and present opportunities and challenges for education. This study conducted a systematic literature review (SLR) of 121 peer-reviewed articles published between 2018 and 2023, offering a comprehensive overview of the current research on genAI in education. It explores the applications and benefits, limitations, risks and concerns, the educational levels addressed, future recommendations, and the genAI tools mentioned in the literature. The findings reveal that genAI has the potential to transform education by offering personalised learning experiences, real-time feedback, and support for educators in lesson planning and content generation. On the other hand, significant concerns have emerged, including the risk of academic dishonesty, over-reliance on AI tools, and a potential decline in students' critical thinking and problemsolving skills. Additionally, issues related to misinformation, biased content, and ethical considerations emphasise the need for a cautious and well-regulated integration of genAI in educational settings. Recommendations are provided for institutions to integrate these tools while mitigating associated risks effectively. This includes incorporating AI into the curriculum, updating assessment methods to prevent academic misconduct, and encouraging a balanced use of technology that complements traditional teaching practices. This research offers a valuable perspective on the evolving role of genAI in education, providing insights for educators, institutions, and researchers.